Mixed calcium-increasing thermally activated loess and preparation method and application thereof, modified loess cement-based cementing material and application thereof, and modified loess cement-based cementing hydrated material and application thereof

By calcining loess with dolomite and soda ash, mixed calcium-enhancing heat-activated loess is prepared and combined with cement, the problem of low hydration reaction activity of loess is solved, the coagulation performance and compressive strength of grouting materials are improved, and the mining is reduced Cost and CO2 emissions.

CN119241113AActive Publication Date: 2025-01-03TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411426411.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-03
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

During coal mining, the hydration reaction activity of raw material loess is low and cannot meet the requirements of the coagulation performance of grouting materials, resulting in large-scale grouting and mining consumption of a large amount of cement and increasing mining costs.

Method used

By mixing loess with dolomite and soda ash, mixed calcium-enhancing and heat-activated loess are prepared, which improves its hydration reaction activity and combines it with cement to form a modified loess cement-based cementitious material, enhancing its coagulation performance and early water rate of transformation.

Benefits of technology

Improve the hydration reaction activity and gelling performance of modified loess, shorten the gelling time, reduce the amount of cement, reduce CO2 emissions, realize energy saving and emission reduction, and improve the coagulation performance and compressive strength of grouting materials. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241113A_ABST
    Figure CN119241113A_ABST
Patent Text Reader

Abstract

The invention provides mixed calcium-increasing thermally-activated loess, a preparation method and application thereof, a modified loess cement-based cementing material and application thereof, and a modified loess cement-based cementing hydrated material and application thereof, and relates to the technical field of coal mine grouting and water-retention mining. The preparation method comprises the following steps: mixing loess with a calcium-increasing agent, and calcining to obtain mixed calcium-increasing heat-activated loess; the calcium increasing agent comprises dolomite and soda ash; the mass ratio of the loess to the calcium increasing agent is (1.5-2.5): 1; the calcination temperature ranges from 1000 DEG C to 1100 DEG C. The dolomite and the soda ash are utilized to perform calcium-increasing modification on the loess, and the calcining temperature and the use amount of the calcium-increasing agent are controlled, so that the pozzolanic activity of the loess is greatly improved, and the hydration reaction activity when the modified loess is used for preparing the cement-based grouting material is further improved. The mixed calcium-increasing heat-activated loess provided by the invention has a good application prospect in water-retaining grouting mining of mines.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coal mine grouting and water conservation mining, and in particular to mixed calcium-enriched thermally activated loess and a preparation method and application thereof, a modified loess cement-based gelling material and application thereof, and a modified loess cement-based gelling hydration material and application thereof. Background Art

[0002] Groundwater resources and coal resources usually coexist in areas with rich coal reserves, which brings great difficulties to coal mining and groundwater protection. During coal mining, it is necessary to prevent water damage from invading and causing water-permeable coal mine accidents, and to protect groundwater resources as much as possible. Grouting mining technology was born. Large-scale grouting mining consumes a lot of cement and other cementitious materials, significantly increases mining costs, and brings a certain economic burden to mining companies.

[0003] The main oxide components in loess are SiO 2 , CaO and Al 2 O 3 , making it a potential auxiliary cementitious material for grouting. However, the hydration reaction activity of raw loess is low, resulting in the fact that loess alone as an auxiliary cementitious material cannot meet the requirements of the grouting material coagulation performance in engineering. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide mixed calcium-enhanced heat-activated loess and preparation method and application, modified loess cement-based cementitious material and application, modified loess cement-based cementitious hydration material and application. The mixed calcium-enhanced heat-activated loess provided by the present invention has high hydration reaction activity. When used as an auxiliary cementitious material to prepare cement-based grouting materials, it has good performance in coagulation and gelling properties, and can meet the needs of different grouting areas by adjusting the ratio.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing mixed calcium-enhanced thermally activated loess, comprising the following steps:

[0007] The loess is mixed with a calcium-enhancing agent and calcined to obtain mixed calcium-enhanced thermally activated loess;

[0008] The calcium-enhancing agent includes dolomite and soda ash;

[0009] The mass ratio of the loess to the calcium-enhancing agent is 1.5 to 2.5:1;

[0010] The calcination temperature is 1000-1100°C.

[0011] Preferably, the mass ratio of dolomite to soda ash is 1:0.8-1.2.

[0012] Preferably, the calcination holding time is 0.8 to 1.2 hours.

[0013] The present invention also provides mixed calcium-enriched heat-activated loess prepared by the preparation method described in the above technical solution.

[0014] The present invention also provides the use of the mixed calcium-enriched heat-activated loess described in the above technical solution as a gel material.

[0015] The present invention also provides a modified loess cement-based gelling material, comprising a composite gel material and water; the composite gel material comprises cement and the mixed calcium-enhanced heat-activated loess described in the above technical solution.

[0016] Preferably, the mass fraction of the mixed calcium-enhanced heat-activated loess in the composite gel material is 20-50%.

[0017] The present invention also provides a modified loess cement-based gelling hydration material, which is obtained by curing the modified loess cement-based gelling material described in the above technical solution.

[0018] Preferably, the curing temperature is 18-22° C., the humidity is 90-100%, and the time is 3-28 days; and the curing is closed curing.

[0019] The present invention also provides the use of the modified loess cement-based gelling material described in the above technical solution or the modified loess cement-based gelling hydration material described in the above technical solution in grouting and water conservation mining.

[0020] The present invention provides a preparation method of mixed calcium-enhanced thermally activated loess, comprising the following steps: mixing loess with a calcium-enhancing agent, calcining, and obtaining mixed calcium-enhanced thermally activated loess; the calcium-enhancing agent comprises dolomite and soda ash; the mass ratio of the loess to the calcium-enhancing agent is 1.5-2.5:1; and the calcination temperature is 1000-1100°C. The present invention utilizes dolomite and soda ash to perform calcium-enhanced modification on loess, and controls the calcination temperature and the amount of the calcium-enhancing agent. During the high-temperature calcination process, the calcium-enhancing agent promotes more aluminum to participate in the solid phase reaction and exists in the calcined product in the form of aluminate and / or metaaluminate, such as Na capturing Al to form NaAlO 2 , while Ca captures Al to form Ca 7 AlO1 2 (OH) 4· 4H 2O, which increases the ion dissolution concentration of Al in the mixed calcium-enhanced heat-activated loess under alkaline conditions; in addition, under high temperature conditions, f-CaO combines with Si in the loess to form a water-hardening calcium silicate product, which increases the Si dissolution in the mixed calcium-enhanced heat-activated loess under alkaline conditions. Therefore, the increase in active ingredients in the calcined product greatly increases the hydration reaction activity of the modified loess, thereby increasing the hydration reaction activity of the modified loess when preparing cement-based grouting materials, and improving the gelling properties of the modified loess. Moreover, the present invention uses dolomite and soda ash to perform calcium-enhanced modification on loess, which increases the early hydration rate of the modified loess for preparing grouting filling materials, and further improves the early gelling properties of the modified loess. The mixed calcium-enhanced heat-activated loess provided by the present invention has a good application prospect in mine water-retaining grouting mining.

[0021] As shown in the test results of the embodiment, compared with the single calcium-enhanced modified loess obtained by modifying dolomite, the mixed calcium-enhanced heat-activated loess modified by dolomite and soda ash in the present invention has a greatly improved dissolution concentration of active Si and Al in an alkaline environment, with the ion dissolution concentration of Si increasing by about 93.54% and the ion dissolution concentration of Al increasing by about 33.42%. It shows that the mixed calcium-enhanced heat-activated loess prepared by the present invention has high hydration activity.

[0022] Moreover, the preparation method provided by the present invention has a simple process and is simple to operate. Loess, dolomite and soda ash are used as raw materials for mixed calcium-enhanced thermally activated loess. The raw materials are widely available and easy to obtain. The production cost of the mixed calcium-enhanced thermally activated loess is low, it has high economic benefits, and is suitable for industrial production.

[0023] The present invention also provides a modified loess cement-based cementitious material, comprising a composite gel material and water; the composite gel material comprises cement and the mixed calcium-enhanced heat-activated loess described in the above technical solution. The present invention uses cement and mixed calcium-enhanced heat-activated loess as composite gel materials. In the early stage of hydration, the presence of aluminates and sheet aluminates in the mixed calcium-enhanced heat-activated loess helps the cementing system to produce more calcium aluminate, shortening the gelling time of the modified loess cement-based cementitious material, having high gelling performance, having a good effect on the plugging of fractured rock masses, having a good application prospect in water-retaining grouting mining in mines, and achieving the purpose of loess resource utilization. As shown in the test results of the embodiment, compared with the single calcium-enhanced modified loess obtained by adding dolomite modification, the final setting time of the modified loess cement-based cementitious material added with mixed calcium-enhanced heat-activated loess of the present invention is shortened by more than 11.1%. It is explained that the gelling time of the modified loess cement-based cementitious material provided by the present invention.

[0024] Moreover, the present invention uses mixed calcium-enriched heat-activated loess to replace part of the cement as the gel material, which can reduce the amount of cement used; at the same time, the calcination temperature for preparing the mixed calcium-enriched heat-activated loess is lower than the calcination temperature in the cement production process, which reduces CO 2emissions, achieving energy conservation and emission reduction.

[0025] The present invention also provides a modified loess cement-based gelling hydration material, which is obtained by curing the modified loess cement-based gelling material described in the above technical solution. The modified loess cement-based gelling material provided by the present invention is hydrated during curing, and produces more calcium aluminate and gel, so that the microscopic pore structure of the modified loess cement-based gelling hydration material is more compact and the solid particle skeleton structure is strengthened, the compressive strength is high, the mechanical properties are good, and as the curing time is extended, the compressive strength increases steadily, which meets the on-site grouting requirements and has a good application prospect in mine water conservation grouting mining. As shown in the test results of the embodiment, compared with the single calcium-enhanced modified loess obtained by adding dolomite modification, the 3d compressive strength of the modified loess cement-based cementitious hydration material added with mixed calcium-enhanced heat-activated loess in the present invention is increased by more than 34.1%, and the 3d compressive strength can reach 16.24 MPa; the 28d compressive strength is increased by more than 22.3%, and the 28d compressive strength can reach 33.98 MPa, indicating that the modified loess cement-based cementitious hydration material provided by the present invention has high compressive strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a comparison chart of the dissolution concentration of active Si and Al of the mixed calcium-enhanced heat-activated loess (mixed calcium-enhanced) prepared in Example 1 and the dolomite single calcium-enhanced modified loess (single calcium-enhanced) prepared in Comparative Example 1;

[0027] Figure 2 This is a comparison result of the final setting time of the gel materials prepared in Examples 2 to 4 (mixed calcium addition) and Comparative Examples 2 to 4 (single calcium addition);

[0028] Figure 3 The 3-day uniaxial compressive strength test results of the modified loess cement-based grouting gelling hydration materials prepared in Examples 2 to 4 (mixed calcium addition) and Comparative Examples 2 to 4 (single calcium addition);

[0029] Figure 4 This is a graph showing the 28-day uniaxial compressive strength test results of the modified loess cement-based grouting gelling hydration materials prepared by Examples 2 to 4 (mixed calcium addition) and Comparative Examples 2 to 4 (single calcium addition). DETAILED DESCRIPTION

[0030] The invention provides a preparation method of mixed calcium-enhanced heat-activated loess, comprising the following steps: mixing loess with the calcium-enhancing agent described in the above technical solution, and calcining to obtain the mixed calcium-enhanced heat-activated loess; the calcium-enhancing agent comprises dolomite and soda ash.

[0031] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0032] In the present invention, the mass ratio of dolomite to soda ash is preferably 1:0.8-1.2, and in specific embodiments may be 1:0.8, 1:0.85, 1:0.9, 1:0.95, 1:1, 1:1.05, 1:1.1, 1:1.15 or 1:1.2.

[0033] In the present invention, the loess is preferably sieved before use, and the particle size of the sieved loess is preferably 0.4 to 141 μm; the specific surface area of ​​the loess is preferably 368 to 406 m 2 / kg.

[0034] In the present invention, the mass ratio of the loess to the calcium increasing agent is preferably 1.5-2.5:1, and in specific embodiments it can be 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1 or 2.5:1.

[0035] In the present invention, the mixing preferably includes stirring and mixing and ball milling in sequence. In the present invention, the rotation speed of the stirring and mixing is preferably 70 to 90 r / min, more preferably 75 to 85 r / min, and further preferably 80 r / min; the time of the stirring and mixing is preferably 5 to 10 min, more preferably 5 to 8 min, and further preferably 5 to 6 min. In the present invention, the rotation speed of the ball milling mixing is preferably 250 to 350 r / min, more preferably 280 to 320 r / min, and further preferably 300 r / min; the ball-to-material ratio of the ball milling mixing is preferably 0.8 to 1.2:1, more preferably 0.9 to 1.1:1, and further preferably 1:1; the time of the ball milling mixing is preferably 20 to 40 min, more preferably 25 to 35 min, and further preferably 30 min.

[0036] In the present invention, the calcination temperature is preferably 1000-1100°C, more preferably 1050-1100°C, and further preferably 1080-1100°C; the heating rate from room temperature to the calcination temperature is preferably 10-20°C / min, more preferably 12-18°C / min, and further preferably 15°C / min; the calcination holding time is preferably 0.8-1.2h, more preferably 0.9-1.1h, and further preferably 1h.

[0037] The present invention also provides mixed calcium-enriched heat-activated loess prepared by the preparation method described in the above technical solution.

[0038] The present invention also provides the use of the mixed calcium-enriched heat-activated loess described in the above technical solution as a gel material.

[0039] The present invention also provides a modified loess cement-based gelling material, comprising a composite gel material and water; the gel material comprises cement and the mixed calcium-enhanced heat-activated loess described in the above technical solution.

[0040] In the present invention, the mass fraction of the mixed calcium-enhanced heat-activated loess in the composite gel material is preferably 20 to 50%, more preferably 20 to 40%, and further preferably 20 to 35%.

[0041] In the present invention, the cement preferably comprises Portland cement.

[0042] In the present invention, the mass ratio of the composite gel material to water is preferably 1:0.8-1.2, and in specific embodiments may be 1:0.8, 1:0.85, 1:0.9, 1:0.95, 1:1, 1:1.05, 1:1.1, 1:1.15 or 1:1.2.

[0043] In the present invention, the preparation method of the modified loess cement-based cementitious material preferably comprises the following steps: dry-mixing cement and mixed calcium-enriched heat-activated loess, then adding water and mixing again to obtain the modified loess cement-based cementitious material.

[0044] In the present invention, the dry mixing preferably includes stirring mixing, and the rotation speed of the stirring mixing is preferably 70 to 90 r / min, more preferably 75 to 85 r / min, and further preferably 80±2 r / min; the time of the stirring mixing is preferably 5 to 10 min, more preferably 5 to 8 min, and further preferably 5 to 6 min.

[0045] In the present invention, the remixing preferably includes stirring and mixing, and the rotation speed of the stirring and mixing is preferably 95-105 r / min, more preferably 98-102 r / min, and further preferably 100 r / min; the time of the stirring and mixing is preferably 4-5 min, and more preferably 4.5 min.

[0046] The present invention also provides a modified loess cement-based gelling hydration material, which is obtained by curing the modified loess cement-based gelling material described in the above technical solution.

[0047] In the present invention, the modified loess cement-based cementitious material is preferably placed in a mold, sealed, compacted, and then cured. In the present invention, the compaction time is preferably 1 to 2 minutes, more preferably 1 to 1.5 minutes; and the compaction is preferably performed on a vibration table.

[0048] In the present invention, the curing is preferably to place the modified loess cement-based gelling material in a mold and seal it for curing. In the present invention, the curing temperature is preferably 18-22°C, more preferably 19-21°C, and further preferably 20°C; the curing humidity is preferably 90-100%, more preferably 92-98%, and further preferably 95%; the curing time is preferably 3-28 days; and the curing is preferably carried out in a curing box. The present invention performs curing under closed conditions, which can prevent water evaporation during the curing process.

[0049] After the curing is completed, the present invention preferably further comprises demoulding to obtain a modified loess cement-based gelled hydration material. In the present invention, the demoulding preferably comprises demoulding with an air pressure gun, and the demoulding with an air pressure gun in the present invention can ensure the integrity of the sample.

[0050] In the present invention, the 3-day uniaxial compressive strength of the modified loess cement-based cementitious hydration material is preferably >7MPa, more preferably 7.06-16.3MPa, and in specific embodiments it may be 7.06MPa, 11.57MPa or 16.24MPa; the 28-day uniaxial compressive strength of the modified loess cement-based cementitious hydration material is preferably >12MPa, more preferably 12.17-34MPa, and in specific embodiments it may be 12.17MPa, 25.01MPa or 33.98MPa.

[0051] The present invention also provides the use of the modified loess cement-based gelling material or the modified loess cement-based gelling hydration material described in the above technical solution in grouting mining. In the present invention, the grouting mining preferably includes water-retaining grouting mining in mines, and more preferably includes water-retaining grouting mining in coal mines.

[0052] In order to further illustrate the present invention, the calcium-enhancing agent and its application, the mixed calcium-enhanced thermally activated loess and its preparation method and application, the modified loess cement-based gelling material and its application, and the modified loess cement-based gelling hydration material and its application provided by the present invention are described in detail below in combination with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0053] In the following examples, the main chemical components of the loess used are as follows, in terms of mass percentage: CaO 11.663%, SiO 2 58.335%,Al 2 O 3 15.555%, MgO 2.454%, Fe 2 O 3 6.047%, Na 2 O1.211%, K 2 O2.887%, SO 30.178% and other substances 1.67%. The loess is sieved before use. The particle size of the sieved loess is 0.4-141μm and the specific surface area is 368-406m 2 / kg.

[0054] The main chemical components of the dolomite used are as follows: CaO 68.132%, SiO 2 10.904%,Al 2 O 3 2.022%, MgO 16.818%, Fe 2 O 3 1.369%, Na 2 O 0.171%, K 2 O 0.175%, SO 3 0.069% and other substances 0.34%.

[0055] The main chemical components of the silicate cement used are as follows: CaO 64.544%, SiO 2 17.691%,Al 2 O 3 7.399%, MgO 3.037%, Fe 2 O 3 2.597%, Na 2 O 0.296%, K 2 O0.576%, SO 3 3.743% and other substances 0.117%.

[0056] Example 1

[0057] Dolomite and soda ash were mixed in a mass ratio of 1:1 to obtain a mixed calcium-enhancing agent. The mixed calcium-enhancing agent and loess were placed in a mixer in a mass ratio of 1:2, stirred at a speed of 80r / min for 5 minutes, the obtained composite powder was placed in a grinder, ground at a speed of 300r / min for 30 minutes, and the ground composite powder was placed in a muffle furnace, heated from room temperature to 1100°C at a heating rate of 15°C / min, and then calcined for 1 hour to obtain a mixed calcium-enhanced thermally activated loess, whose mineral composition is mainly tricalcium silicate (C 3 S), dicalcium silicate (C 2 S), calcium heptadecanedaluminate (C 12 A 7 ), calcium aluminate (CA), quartz (SiO 2 ), mullite (AS), lime (CaO), etc. Among them, the grinding ball-to-material ratio is 1:1.

[0058] Example 2

[0059] The mixed calcium-enhanced heat-activated loess and silicate cement prepared in Example 1 were put into a mixer in a mass ratio of 2:8, and stirred at a speed of 80±2r / min for 5 minutes to obtain a grouting cementitious material powder. Water was added, and stirred at a speed of 100r / min for 4.5 minutes. The powder was injected into a cylindrical mold with a closed lower opening, the upper opening was closed, and the powder was compacted on a vibration table for 1 minute to obtain a modified loess cement-based grouting cementitious material.

[0060] The modified loess cement-based grouting gelling material is placed in a curing box, sealed and cured for 3 to 28 days at 20° C. and 95% humidity, and demolded with an air pressure gun to obtain a modified loess cement-based grouting gelling hydration material. The mass ratio of the grouting gelling material powder to water is 1:1.

[0061] Example 3

[0062] Modified loess cement-based grouting gelling material and modified loess cement-based grouting gelling hydration material were prepared according to the method of Example 2, the only difference from Example 2 being that the mass ratio of mixed calcium-enhanced heat-activated loess to silicate cement was 3.5:6.5.

[0063] Example 4

[0064] Modified loess cement-based grouting gelling material and modified loess cement-based grouting gelling hydration material were prepared according to the method of Example 2, the only difference from Example 2 being that the mass ratio of mixed calcium-enhanced heat-activated loess to silicate cement was 5:5.

[0065] Comparative Example 1

[0066] Dolomite and loess were placed in a mixer at a mass ratio of 1:2, stirred at 80 r / min for 3 min, the resulting composite powder was placed in a grinder, ground at 300 r / min for 30 min, the ground composite powder was placed in a muffle furnace, heated from room temperature to 825°C at a heating rate of 15°C / min, and then calcined for 1 h to obtain dolomite single calcium-enhanced modified loess. The grinding ball-to-material ratio was 1:1.

[0067] Comparative Example 2

[0068] The only difference from Example 2 is that the mixed calcium-enhanced heat-activated loess is replaced by the dolomite single calcium-enhanced modified loess prepared in Comparative Example 1.

[0069] Comparative Example 3

[0070] The only difference from Example 3 is that the mixed calcium-enhanced heat-activated loess is replaced by the dolomite single calcium-enhanced modified loess prepared in Comparative Example 1.

[0071] Comparative Example 4

[0072] The only difference from Example 4 is that the mixed calcium-enhanced heat-activated loess is replaced by the dolomite single calcium-enhanced modified loess prepared in Comparative Example 1.

[0073] Test Example 1

[0074] 1. Volcanic ash activity test

[0075] Test method: Take 1g of calcined sample and 100ml of NaOH solution (1mol / L) and put them into a 200ml plastic test tube, and keep the test tube in a constant temperature (20℃) water bath oscillator for 7 days; use 0.45μm filter paper to filter the mixed solution to obtain the supernatant; use inductively coupled plasma optical emission spectrometry (ICP-OES) to test the dissolution concentration of Si and Al ions in the filtrate to evaluate the volcanic ash activity of the material.

[0076] Figure 1 The figure is a comparison of the dissolution concentrations of active Si and Al of the mixed calcium-enhanced heat-activated loess (mixed calcium-enhanced) prepared in Example 1 and the dolomite single calcium-enhanced modified loess (single calcium-enhanced) prepared in Comparative Example 1. It can be seen that compared with the dolomite single calcium-enhanced modified loess prepared in Comparative Example 1, the alkaline environment dissolution concentrations of active Si and Al prepared by the mixed calcium-enhanced heat-activated loess of the present invention are greatly improved, and the ion dissolution concentration of Si increases by about 93.54%, which is because f-CaO combines with more active Si at high temperature to form calcium silicate products with water hardness; the ion dissolution concentration of Al increases by about 33.42%, mainly because Na captures more Al to form NaAlO 2 .

[0077] 2. Coagulation time test

[0078] Test method: Use the Vicat instrument to test the setting time of the slurry. Install a ring attachment on the final setting needle. After the slurry is initially set, immediately turn the test mold connected to the slurry 180° in a translational manner, with the large end facing up and the small end facing down on the bottom plate, and then put it in the moisture box for further curing. During temporary final setting, measure once every 15 minutes. When the test needle sinks into the specimen by 0.5mm, that is, the ring attachment begins to leave no trace on the specimen, the cement has reached the final setting state. When the final setting state is reached, the measurement should be repeated immediately. When the two results are the same, the grouting liquid has reached the final setting state.

[0079] Figure 2The final setting time comparison result diagram of the gel materials prepared by Examples 2 to 4 (mixed calcium addition) and Comparative Examples 2 to 4 (single calcium addition) shows that, compared with the modified loess cement-based grouting gelling materials prepared by Comparative Examples 2 to 4, the final setting time of the modified loess cement-based gelling hydration material prepared by the present invention is shortened by 11.1%, 19.4% and 31.0%, respectively, and the final setting time is significantly reduced. This is mainly because when the mixed calcium addition is calcined, more active aluminum participates in the solid phase reaction and exists in the calcined product in the form of aluminate and metaaluminate, which helps the gelling system to produce more calcium aluminate in the initial hydration stage with cement, thereby shortening the gelling time.

[0080] 3. 3d and 28d uniaxial compressive strength test

[0081] Test method: The cured test blocks that have reached the pre-curing time (3d and 28d) are subjected to uniaxial compression tests. The uniaxial press machine is the Humboldt HM-5030 test machine produced in the United States, with a maximum loading capacity of 50kN. According to the ASTM C39 / C39M-18 standard, the loading speed during the test is 1mm / min, and the displacement loading method is used. Before the test, both ends of the test block are kept as flat as possible, and vaseline is applied to reduce the influence of end friction. At least three test blocks are tested and the average value is taken as the final compressive strength value.

[0082] Figure 3 The 3-day uniaxial compressive strength test results of the modified loess cement-based grouting gelling hydration materials (size 50 mm×100 mm) prepared in Examples 2 to 4 (mixed calcium addition) and Comparative Examples 2 to 4 (single calcium addition) are shown in FIG. Figure 4 The 28-day uniaxial compressive strength test results of the modified loess cement-based grouting gelling hydration materials (size 50mm×100mm) prepared in Examples 2 to 4 (mixed calcium addition) and Comparative Examples 2 to 4 (single calcium addition) are shown. It can be seen that compared with the materials prepared in Comparative Examples 2 to 4, the 3d compressive strength of the modified loess cement-based grouting gelling hydration materials prepared by the present invention is increased by 34.1%, 40.2% and 36.8%, respectively, and the 28d compressive strength is increased by 22.3%, 24.4% and 24.1%, respectively. The uniaxial compressive strength values ​​of 3d and 28d are increased to a certain extent. This is mainly because the gelling system of the material prepared by the present invention is hydrated to produce more calcium aluminate and gel, making the microscopic pore structure more compact and the solid particle skeleton structure strengthened, and the mechanical properties increased.

[0083] In summary, the mixed calcium-enhanced heat-activated loess prepared by the present invention has better hydration activity, and the modified loess cement-based grouting cementitious material prepared with cement and water has a short setting time, which is conducive to rapid construction, and has high cementing performance, which has a better effect on sealing fractured rock masses. Moreover, the modified loess cement-based grouting cementitious hydration material prepared by the present invention has high strength.

[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing mixed calcium-enriched thermally activated loess, comprising the following steps: The loess is mixed with a calcium-enhancing agent and calcined to obtain mixed calcium-enhanced thermally activated loess; The calcium-enhancing agent includes dolomite and soda ash; The mass ratio of the loess to the calcium-enhancing agent is 1.5 to 2.5:1; The calcination temperature is 1000-1100°C.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the dolomite to soda ash is 1:0.8-1.

2.

3. The preparation method according to claim 1 or 2, characterized in that: The calcination holding time is 0.8 to 1.2 hours.

4. Mixed calcium-enriched heat-activated loess prepared by the preparation method according to any one of claims 1 to 3.

5. Use of the mixed calcium-enriched heat-activated loess described in claim 4 as a gel material.

6. A modified loess cement-based gelling material, comprising a composite gel material and water; the composite gel material comprises cement and the mixed calcium-enhanced heat-activated loess according to claim 4.

7. The modified loess cement-based gelling material according to claim 6, characterized in that: The mass fraction of the mixed calcium-enhanced heat-activated loess in the composite gel material is 20-50%.

8. A modified loess cement-based gelling hydration material obtained by curing the modified loess cement-based gelling material according to claim 6 or 7.

9. The modified loess cement-based gelling hydration material according to claim 8, characterized in that: The curing temperature is 18-22° C., the humidity is 90-100%, and the time is 3-28 days; and the curing is closed curing.

10. Use of the modified loess cement-based gelling material according to any one of claims 6 to 7 or the modified loess cement-based gelling hydration material according to any one of claims 8 to 9 in grouting mining.

Citation Information

Patent Citations

  • Composite additive

    CN105567375A

  • Grouting filling material and preparation method thereof

    CN114436618A

  • All-solid waste composite filling cementing material prepared from waste glass and method

    CN115353360A

  • Coal mine filling material based on loess composite curing agent and preparation method thereof

    CN120058333A

  • Manufacturing method of eco mortar containing red clay

    KR101993114B1